Beyond Ending Poverty : The Dynamics of Microfinance in Bangladesh - Khandker, Shahidur R.; Khalily, M.A. Baqui; Samad, Hussain A. (2016)
The recent past has witnessed phenomenal growth in MFIs around the world. Today as many as 200 million people are beneficiaries of microfinance. Given its worldwide attention, microfinance has received serious criticism, including the argument that it is a fad with less-than-expected benefits for the poor. Surely, microfinance is not without any pitfalls. Yet the premise of improving access to financial services for consumption smoothing by the poor has never been a subject of controversy. What has been controversial is whether microfinance can alleviate poverty. That the poor lack an effective and affordable alternative financing mechanism to support income generation does not necessarily mean microfinance is a panacea since it involves entrepreneurial skills, which many poor lack. It is little wonder that studies evaluating the benefits of microfinance have produced conflicting results. Of course, study findings are contextual: They are positive in conducive environments and less so in unfavorable ones. Microfinance must be distinguished from anti-poverty schemes (e.g., conditional cash transfers) because benefits from microfinance-supported activities, which involve participants’ entrepreneurial skills and ability, take time to realize.